Knjižnično informacijsko znanje v poklicnem in srednjem strokovnem izobraževanju - Mrak, Katja (Šolska knjižnica, 2016)
Since the development of information literacy is still poorly supported in primary schools, the teaching of information skills is one of the key tasks of secondary schools. Research has shown that more than half of a school librarian's working hours are devoted to direct educational work. Hence the school librarian carries great responsibility; his/her work is aided by the librarian's competences, professional knowledge, skills, the ability to motivate, and education. When teaching library and information knowledge (KIZ) in secondary and technical schools, one must consider the number of specific features that separate such students from general secondary school students. Frontal instruction will achieve very little with such students; each theoretical part must be at least partly connected with practice; due to their lack of concentration, the lessons must be carried out in a way that keeps the students active most of the time.
Keywords: informacijska pismenost; knjižnično informacijsko znanje; srednje šole; šolske knjižnice; šolski knjižničarji